The annual Day of the Dead song contest: musical‐linguistic ideology and practice, piratability, and the challenge of scale. (June 2014) - Faudree, Paja
<x xml:space="preserve">Abstract</x> Building on research theorizing scale, this article proposes augmentations to existing frameworks that will help illuminate how localities are linked to 'stranger collectives' like nations, ethnicities, and global religious 'communities'. In this case of ethnic revival from Mexico's Sierra Mazateca, people use new vernacular literacy practices tied to local musical performances as a way of 'customizing' modular forms deployed by national and global institutions to manage indigenous difference. People 're‐imagine' locality through a localized indigenous literacy that takes templates provided by the Mexican state and the Catholic Church and places them in productive tension with local context: musical properties of the indigenous language Mazatec, locally valued performance practices, and local musical‐linguistic ideologies. While this revival movement draws on immanently modular forms, once locally embedded they become 'unpiratable', and constitute a new resource for inscribing local belonging. This case suggests the importance of considering linguistic and musical aspects of social context often taken for granted in anthropological investigations of scale.